2009
DOI: 10.1523/jneurosci.1121-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Axon Initiation and Growth Cone Turning on Bound Protein Gradients

Abstract: Extracellular gradients of secreted guidance factors are known to guide axon pathfinding and neuronal migration. These factors are likely to bind to cell surfaces or extracellular matrix, but whether and how they may act in bound gradients remains mostly unclear. In this study, we have developed a new technique for rapid production of stable microscopic gradients of substrate-bound proteins by covalent bonding of the proteins with an epoxy-coated glass substrate while they are diffusing in an agarose gel. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
114
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(122 citation statements)
references
References 46 publications
6
114
1
1
Order By: Relevance
“…Next, we generated a gradient of bound laminin using diffusive printing method [33,34] to mimic the potential cortical distribution of laminin [19]. As shown in Figure 2E, the bound laminin gradient was confirmed by immunostaining with anti-laminin antibody.…”
Section: Patterned Laminin and Itgb1 Are Necessary For Oriented Axon mentioning
confidence: 97%
See 1 more Smart Citation
“…Next, we generated a gradient of bound laminin using diffusive printing method [33,34] to mimic the potential cortical distribution of laminin [19]. As shown in Figure 2E, the bound laminin gradient was confirmed by immunostaining with anti-laminin antibody.…”
Section: Patterned Laminin and Itgb1 Are Necessary For Oriented Axon mentioning
confidence: 97%
“…Diffusive printing assay was performed to generate bound substrate gradient as described previously [34] with some modifications. Briefly, silicon molds with parallel grooves, each 350 µm in width, 100 µm in depth, and 4 mm apart, were designed and produced by using standard photolithography.…”
Section: Diffusive Printing Assaymentioning
confidence: 99%
“…Although BDNF/TrkB signaling has been previously shown to elevate cAMP and calcium levels in neurons (1,42), it is believed to occur and remain local, such as neurite terminals (20). However, it is clear that elevation of intracellular cAMP or calcium facilitate the functional and morphological synaptic responses to BDNF signaling (43,44). Elevation of intracellular calcium activates calcineurin whereas cAMP activates PKA, which in turn phosphorylates and deactivates the upstream CRTC kinase, salt-inducible kinase (SIK).…”
Section: Activation Of An Essential Creb Co-activator Through Dephospmentioning
confidence: 99%
“…In particular, cyclic nucleotide levels can influence the sign of the chemotactic response Song et al, 1997;Song et al, 1998;Wen et al, 2004;Mai et al, 2009;Murray et al, 2009;Tojima et al, 2009). It has been shown that high levels of cAMP relative to cGMP lead to growth cone attraction, while the opposite leads to repulsion (Nishiyama et al, 2003).…”
Section: Introductionmentioning
confidence: 99%